From the bottom 40 to inequality lines: Sharing prosperity globally and domestically - Borja Lopez-Noval; Miguel Ni\~no-Zarazúa; Laurence Roope; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
A major of focus of global development policy is the aim to achieve and sustain income growth of the bottom 40% (B40) of the population at a rate higher than the national average. We propose an alternative approach to assessing shared prosperity using 'inequality lines'. Analogous to poverty lines but focused on inequality, inequality lines are benchmark incomes. Income increases below the inequality line decrease inequality; income increases above the line increase inequality. In contrast to the B40 approach and all conventional poverty lines, inequality lines arise naturally: their location in the income distribution is directly implied by standard inequality indexes and the social preferences they embody. Using inequality lines, we investigate the extent to which there may be trade-offs between sharing prosperity domestically and sharing prosperity globally. With data from the World Income Inequality Database, we present the most comprehensive empirical study to date of where inequality lines lie and how they evolved during 1950-2020. With estimates for 208 countries in 2020, we provide the first estimates of global inequality lines, how the global inequality line percentile changed over time, and how it compares with domestic inequality lines. Our results reveal when income growth, subsidies, or developmental interventions are likely to reduce inequality both domestically and globally, and where there are trade-offs between the two. We also shed light on important domestic trade-offs between inequality reduction and poverty alleviation.
Keywords: D31; D63; O15; 330; benchmark incomes; global inequality; global poverty; inequality; inequality lines; poverty; shared prosperity